Accelerating the Innovation Uptake in Logistics - Nils Meyer-Larsen; Jannicke Baalsrud Hauge; Rainer Müller; Kahina Hamadache; Georgia Aifadopoulou; Margherita Forcolin; Violeta Roso; George Tsoukos; Hans Westerheim (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
During the last decades several research projects and related initiatives have investigated innovative approaches and solutions aiming at improving transport logistics. However the level of adoption has still not reached a satisfactory level. In fact, compared with other industry sectors it is very low. The European Union (EU)-funded project Loginn - Logistic Innovation Uptake - aims at investigating the reasons behind this and to develop methodologies for overcoming the slow innovation uptake in the field of logistics. As an example, for research and development projects in the logistics area the idea is to improve their capabilities to bridge the gap between pilot implementation and marketable solutions. For this purpose, the project will examine existing approaches of innovation achievement. Combined with the identified barriers and gaps currently hindering innovation in the logistics sector, this will serve as an input that culminates in a Logistics Innovation Action Plan for Europe integrating existing initiatives for accelerating logistics innovation market uptake into a comprehensive, straightforward form with a precise initiatives-to-do list. In addition, the project aims at disseminating innovative logistics practices, technologies and business models to the logistics community and fostering the information exchange on innovation in logistics. For this purpose, an information hub for logistics innovation, the "LogisticsArena" (www.logisticsarena.eu), was established, which is supported by additional activities on social media like Facebook, LinkedIn and Twitter. This paper presents first results of the project.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; maritime piracy; anti-piracy measures; effectiveness; commercial shipping